Interação entre o gene TKN2 (KNOX-type I) e o miR156 node durante a transição de fase vegetativa para reprodutiva em tomateiro (Solanum lycopersicum) - Corazon-Guivin, Mike Anderson [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Plant development depends on the activity of a group of dividing cells called meristem. Extensive genetic analyses have identified the major regulators of the shoot apical meristem (SAM), which control the development of all aerial organs. Among them, the three-amino-acid- loop-extension (TALE) class of homeoproteins; this family contains the KNOTTED-like homeodomain (KNOX) and BELL-like Homeodomain (BELL) members, which function as heterodimers or homodimers, to regulate expression of their target genes by binding to specific sequences in DNA. In plants with compound leaves as tomato (Solanum lycopersicum), KNOX I are expressed in the meristem, as well as on leaves, flowers and fruits, suggesting that they may play various roles in these organs. This hypothesis is supported by the intriguing phenotypes found in mutants with gain-of function of KNOX I genes, whose ectopic expression affects leaf, petal and fruit shape. An example, is the tomato mutant Mouse ear (Me), which overexpress the gene TKN2 (KNOX I). Similar phenotypes were also observed in transgenic plants overexpressing microRNA156 (miR156). MicroRNAs are a class of small no-coding RNAs (20-25 nucleotides) that are widely distributed in the genome of plants and animals, regulating the expression of their target genes by acting mainly at the post-transcriptional level. miR156 regulated post-transcriptionally most SQUAMOSA Promoter-Binding Protein-Like (SPL or SBP-box) genes, which encode plant-specific transcription factors. These genes play important roles in different aspects of development. To examine a possible molecular interaction between TKN2 transcription factor and microRNA156/SQUAMOSA Promoter-Binding Protein-Like module (miR156 node), it was evaluated the expression of miR156, its targets (SBP-box) and several genes downstream of miR156 node in different stages of the development of homozygous Me plants. Moreover, to evaluate the genetic interaction ...

O desenvolvimento das plantas depende da atividade de um grupo de células em divisão chamado de meristema. Extensas análises genéticas identificaram os principais reguladores do meristema apical vegetativo (SAM), os quais controlam o desenvolvimento de todos os órgãos aéreos. Dentre eles, há um grupo de homeoproteínas denominadas TALE (three-amino-acid-loop- extension); esta família contém os membros KNOTTED-like homeodomain (KNOX) e BELL-like Homeodomain (BELL), que funcionam como homodímeros ou heterodímeros, para regular a expressão de seus genes alvos mediante sua ligação à sequências especificas no DNA. Em plantas com folhas compostas como o tomateiro (Solanum lycopersicum), genes KNOX da classe I (KNOX I) são expressos no meristema, assim como também em folhas, flores e frutos, sugerindo que eles podem exercer várias funções nestes órgãos. Esta hipótese é corroborada pelos fenótipos intrigantes encontrados em mutantes com ganho de função dos genes KNOX I, cuja expressão ectópica afeta a forma da folha, pétala e frutos. Um exemplo é o tomateiro mutante Mouse ear (Me), que superexpressa o gene TKN2 (KNOX I). Fenótipos semelhantes também foram observados em plantas transgênicas superexpressando o microRNA156 (miR156). Os MicroRNAs são uma nova classe de pequenas moléculas de RNA não codantes (20-25 nucleotídeos) que se encontram amplamente distribuídos no genoma de plantas e animais, regulando a expressão de seus genes alvos principalmente ao nível pós-transcricional. O miR156 regula pós-transcricionalmente membros da família gênica do tipo SQUAMOSA Promoter-Binding Protein-Like (SPL ou SBP-box), os quais codificam fatores de transcrição específicos de plantas. Tais genes desempenham papéis importantes em diferentes aspectos do desenvolvimento. Para analisar a possível interação molecular entre o fator de transcrição TKN2 e a via microRNA156/SQUAMOS Promoter-Binding ...
Keywords: Plantas - Reprodução; Tomate - Melhoramento genético; Expressão gênica; Meristema; Reguladores de crescimento; Codigo genético; Gene expression